2006
DOI: 10.1016/j.ijfoodmicro.2006.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of heat-injured Listeria innocua

Abstract: Listeria innocua was subjected to thermal inactivation and the extent of heat-injured cells was quantified. Cultures were heated in liquid medium for different times, using temperatures in the range of 52.5 to 65.0 degrees C, and plated on Tryptic Soy Agar with 0.6% yeast extract (TSAYE) used as non-selective medium and on TSAYE plus 5% NaCl (TSAYE+NaCl) and Palcam agar with selective supplement (Palcam agar) as selective media. The difference observed in counts in non-selective and in selective media gave an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…In our work, the microbial inactivation parameters commonly used in food technology, D and z values, were comparable to those obtained by other authors under similar conditions (4,5,11,12,15,23) Variability in D values has been analyzed extensively by van Asselt and Zwietering (28), who compared 4,066 D values for pathogens and observed that most factors reported to affect the D value have an influence that is less than the variability of all published D values.…”
Section: Discussionsupporting
confidence: 88%
“…In our work, the microbial inactivation parameters commonly used in food technology, D and z values, were comparable to those obtained by other authors under similar conditions (4,5,11,12,15,23) Variability in D values has been analyzed extensively by van Asselt and Zwietering (28), who compared 4,066 D values for pathogens and observed that most factors reported to affect the D value have an influence that is less than the variability of all published D values.…”
Section: Discussionsupporting
confidence: 88%
“…The ability of selective enrichment broth to resuscitate temperature-, preservative-, salt-, and acid-stressed cells (1,3,33,36) encountered during food processing, storage, or sanitization is critical for detection. It is also well known that injured cells can cause an improper estimation of the decimal reduction time (D value) and z value (temperature required to change the D value to transverse by 1 log) during thermal processing (41) and, most importantly, that the injured pathogens can revive and grow under favorable conditions (9). We have demonstrated that SEL allowed the recovery of acid (pH 5.5)-and temperature (4°C)-stressed cells and that, overall, the recovery rates were comparable to those in nonselective TSBYE broth (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were removed from the stirred TSBYE at different time intervals and immediately placed in a mixture of ice-water. Samples were serially diluted and plated in duplicate onto three different media: (i) TSAYE, (ii) TSAYE supplemented with 5% (w/v) sodium chloride -TSAYE + NaCl and (iii) Palcam Agar plus selective supplement (Miller, Brandao, Teixeira, & Silva, 2006). Plates were incubated at 30°C…”
Section: Log Reduction Experiments In Brothmentioning
confidence: 99%